Implementation Of The Policy On The Implementation Of The Information System For The Development Of The Auditor's Functional Position in The Kotamobagu Regional Inspectorate - Siwu, Siska Nellia; Masengi, Evi Elvira; Dilapanga, Abdul Rahman (JUPE : Jurnal Pendidikan Mandala, 2023)
This research aims to describe and analyze the implementation of the Functional Auditor Position Development Information System at the Kotamobagu Regional Inspectorate. This research used a descriptive qualitative approach with a predetermined number of 4 (four) people consisting of Regional Inspectors and several existing SIBIJAK auditor and admin functional positions. The data collection techniques used are interviews and observation as well as documentation with data analysis techniques through data reduction, data presentation and drawing conclusions. The results of this research were obtained in the research focus on the implementation of the Information System for the Development of Functional Auditor Positions in the Kotamobagu Regional Inspectorate through 3 (three) research sub-focuses which include, (1) Implementation of the Information System for Functional Auditor Positions in the Kotamobagu Regional Inspectorate, (2) Readiness of facilities and infrastructure and resources at the Kotamobagu Regional Inspectorate in adapting to system demands, (3) Availability of communication media for complaints about SIBIJAK. Most of the human resources at the Kotamobagu Regional Inspectorate have been able to adapt to the demands of technological progress as promoted by SIBIJAK. In the sub-focus, the complaint media provided in SIBIJAK has not been able to accommodate incoming complaints quickly and accurately. Where there is a complaint submitted in SIBIJAK but after 10 (ten) days there has been no follow-up on the complaint.